Is Research on Children's Preconceptions a Suitable Issue for Students in their Thesis? The Example of the Origin of Lake Constance Shows Results of a Student Evaluation in Primary Geography Education - Wustmann, Kathrin; Schleicher, Yvonne (Journal of Geography Education, 2009)
By using the mental model-building strategy, authors such as Sibylle Reinfried, Stephan Schuler and Kerstin Drieling have shown in their research, that preconceptions concerning geographic issues can be identified. Therefore the question arose, whether their research-approach could be used in a modified or simplified way by students of geographic education in primary schools. Within the framework of their exams these students have to conduct a thesis, based on empirical research. After evaluating the results of a group of students it seems to be obvious, that this approach contributes substantially to the professional development of geography teachers.